Problems in the mastery of reading skills among students of Tongxin Arabic College of Ningxia and the solutions - Li, Ziyun (2020)
This study was conducted to analyze the problems in the mastery of reading skills among students at Tongxin Arabic College of Ningxia in China and the recommended solutions. A total of 100 students and 12 teachers at Tongxin Arabic College of Ningxia were selected as the study sample. Questionnaire, interview and observation instruments were used for data collection purposes. The data obtained were analyzed using Statistical Package for the Social Science (SPSS) version 26. The quantitative data were analyzed using a simple descriptive method and reported in frequency and percentage. The findings from the questionnaire instrument showed that 75% of the students were having problems in mastering Arabic reading skills well. In addition, through observation and interview protocols, the data demonstrated that there were three factors that could influence the mastery of reading skills among students, namely self-motivation; learning and teaching strategies; and the size of vocabulary mastery. In order to overcome the problems in the mastery of reading skills among students, this study also recommends some alternative methods that are suitable to be applied in Tongxin Arabic College of Ningxia. 11 is hoped lhat this study will be able to help the authorities to boost the mastery of reading skills among students at Tongxin Arabic College of Ningxia in China, in particular, as well as all other countries that are not native speakers of the Arabic language, in general